Podocyte Injury in Diabetic Kidney Disease: A Focus on Mitochondrial Dysfunction - Liu, Simeng; Yuan, Yanggang; Xue, Yi; Xing, Changying; Zhang, Bo (Frontiers in Cell and Developmental Biology, 2022)
Podocytes are a crucial cellular component in maintaining the glomerular filtration barrier, and their injury is the major determinant in the development of albuminuria and diabetic kidney disease (DKD). Podocytes are rich in mitochondria and heavily dependent on them for energy to maintain normal functions. Emerging evidence suggests that mitochondrial dysfunction is a key driver in the pathogenesis of podocyte injury in DKD. Impairment of mitochondrial function results in an energy crisis, oxidative stress, inflammation, and cell death. In this review, we summarize the recent advances in the molecular mechanisms that cause mitochondrial damage and illustrate the impact of mitochondrial injury on podocytes. The related mitochondrial pathways involved in podocyte injury in DKD include mitochondrial dynamics and mitophagy, mitochondrial biogenesis, mitochondrial oxidative phosphorylation and oxidative stress, and mitochondrial protein quality control. Furthermore, we discuss the role of mitochondria-associated membranes (MAMs) formation, which is intimately linked with mitochondrial function in podocytes. Finally, we examine the experimental evidence exploring the targeting of podocyte mitochondrial function for treating DKD and conclude with a discussion of potential directions for future research in the field of mitochondrial dysfunction in podocytes in DKD.